Fifth street skid row - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1973)
This film offers a candid excursion into the lives of the men who live around Fifth Street in down town L.A. Through short interviews with men, viewers learn what life is like on skid row
Keywords: Skid row -- Los Angeles; Slums -- Los Angeles; Squatter settlements -- Los Angeles